PEMANFAATAN TELEKONFEREN SEBAGAI ALAT BANTU PEMBUKTIAN DALAM PERSIDANGAN PIDANA - Sulistyawati, Putu Elik; Sujana, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013)
As we know the technology has recently created a sophisticated and increasinglydiverse that can facilitate the work of man. This of course brings a positive and negativeimpact to the development of the future of human civilization. One of the media’s livelydiscussion that is teleconference. With media teleconference one can communicate in audiovisual without knowing the distance and time. When associated with proof of course withthe teleconference technology helps the process of proof in criminal cases, which willshorten the time resolution of the matter.
Keywords: Teleconference, Proof, Criminal Trial.